FEATURE EXTRACTION AND SUPERVISED LEARNING FOR VOLATILE ORGANIC COMPOUNDS GAS RECOGNITION - Mohd Tombel, Nor Syahira; Mohd Zaki, Hasan Firdaus; Mohd Fadglullah, Hanna Farihin (IIUM Engineering Journal, 2023)
The emergence of advanced technologies, particularly in the field of artificial intelligence (AI), has sparked significant interest in exploring their potential benefits for various industries, including healthcare. In the medical sector, the utilization of sensing systems has proven valuable for diagnosing pulmonary diseases by detecting volatile organic compounds (VOCs) in exhaled breath. However, the identification of the most informative and discriminating features from VOC sensor arrays remains an unresolved challenge, essential for achieving robust VOC class recognition. This research project aims to investigate effective feature extraction techniques that can be employed as discriminative features for machine learning algorithms. A preliminary dataset was used to predict VOC classification through the application of five supervised machine learning algorithms: k-Nearest Neighbors (kNN), Random Forest (RF), Support Vector Machines (SVM), Logistic Regression (LR), and Artificial Neural Networks (ANN). Ten feature extraction methods were proposed based on changes in sensor response as inputs to classify three types of gases in the dataset. The performance of each model was evaluated and compared using k-Fold cross-validation (k=10) and metrics derived from the confusion matrix. The results demonstrate that the RF model achieved the highest mean accuracy and standard deviation, with values of 0.813 ± 0.035, followed closely by kNN with 0.803 ± 0.033. Conversely, LR, SVM (kernel=Polynomial), and ANN exhibited poor performances when applied to the VOC dataset, with accuracies of 0.447 ± 0.035, 0.403 ± 0.041, and 0.419 ± 0.035, respectively. Therefore, this paper provides evidence that classifying VOC gases based on sensor responses is feasible and emphasizes the need for further research to explore sensor array analysis to enhance feature extraction techniques. ABSTRAK: Perkembangan teknologi canggih, khususnya dalam bidang kecerdasan buatan (AI), telah mencetuskan minat yang ketara dalam menerokai manfaatnya untuk pelbagai industri, termasuk bidang kesihatan. Dalam sektor perubatan, penggunaan sistem penderiaan telah terbukti bernilai untuk mendiagnosis penyakit paru-paru dengan mengesan sebatian organik meruap (VOC) dalam nafas yang dihembus manusia. Walau bagaimanapun, pengenalpastian ciri yang paling bermaklumat dan mendiskriminasi daripada penderia VOC kekal sebagai cabaran yang tidak dapat diselesaikan, penting untuk mencapai pengiktirafan kelas VOC yang kukuh. Projek penyelidikan ini bertujuan untuk menyiasat teknik pengekstrakan ciri yang berkesan yang boleh digunakan sebagai ciri diskriminatif untuk algoritma pembelajaran mesin. Set data awal digunakan untuk meramalkan klasifikasi VOC melalui aplikasi lima algoritma pembelajaran mesin yang diselia: k-Nearest Neighbors (kNN), Random Forest (RF), Support Vector Machines (SVM), Logistic Regression (LR), dan Artificial Neural Networks (ANN). Sepuluh kaedah pengekstrakan ciri telah dicadangkan berdasarkan perubahan dalam tindak balas penderia sebagai input untuk mengklasifikasikan tiga jenis gas dalam set data. Prestasi setiap model telah dinilai dan dibandingkan menggunakan pengesahan silang k-Fold (k=10) dan metrik yang diperoleh daripada confusion matriks . Keputusan menunjukkan bahawa model RF mencapai ketepatan minima tertinggi dan sisihan piawai, dengan nilai 0.813 ± 0.035, diikuti oleh kNN dengan 0.803 ± 0.033. Sebaliknya, LR, SVM (kernel=Polinomial), dan ANN mempamerkan prestasi yang lemah apabila digunakan pada dataset VOC, dengan ketepatan masing-masing 0.447 ± 0.035, 0.403 ± 0.041 dan 0.419 ± 0.035. Oleh itu, kertas kerja ini memberikan bukti bahawa mengklasifikasikan gas VOC berdasarkan tindak balas penderia adalah boleh dilaksanakan dan menekankan keperluan untuk penyelidikan lanjut untuk meneroka analisis tatasusunan penderia untuk meningkatkan teknik pengekstrakan ciri.